Necessity of Using the Science of Ahangyol (Way of Harmony) in building of economy in terms of modern requirements - Gashamoglu, Ahmad (Archives of Business Research, 2020)
The basic principle of the science of Harmony (science of Ahangyol) is that - if the universe has existed and functioned on the basis of the principle of Harmony for billions of years, regardless of its size, the activity of any being in the universe can be considered appropriate if this activity serves to increase and multiply harmony around itself and in the universe. According to the author, more successful results can be achieved if the modern economic theories and economic mechanisms are also built on the principle of Harmony. The article analyzes the basic principles of modern economic theories, that deals with important issues, should be taken into consideration. One of the most pressing issues in the modern world, as well as in economic projects, is the rapid growth of the world's population. It is highlighted in the article that the challenge of regulating population growth in the world currently is not being successfully addressed. With the help of the science of Harmony (science of Ahangyol), a new model, based on the rules of natural development of society, is proposed to address the challenge. It is scientifically substantiated that modern economic theories can be further improved if we take the proposed model into account and use the science of Harmony (science of Ahangyol), which, in turn, can contribute to a more harmonious development of our societies.